THE EFFECT OF CANVA BASED INTERACTIVE LEARNING MEDIA ON IMPROVING THE NATIONALISM KNOWLEDGE OF INDONESIAN CHILDREN AT SANGGAR BIMBINGAN SUNGAI MULIA MALAYSIA - Dyah Pertiwi Yuni Ningrum; Endang Puspitasari; Ahmad Farid Utsman (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2025)
Instilling a sense of nationalism from an early age presents challenges, especially for Indonesian children living abroad, such as those at Sanggar Bimbingan Sungai Mulia in Malaysia. Limited exposure to national symbols, values, and cultural identity often results in a lack of understanding of their Indonesian roots. This study aims to examine the effectiveness of Canva-based interactive learning media in improving children's knowledge of nationalism.This research used a quantitative approach with a one-group pretest–posttest design involving 25 children aged 5–6 years. A pretest was conducted to assess their initial understanding, followed by lessons using Canva to introduce topics such as national symbols, the anthem, traditional houses, local food, and Pancasila values. A posttest was then given, and the data were analyzed using a paired sample t-test.The results showed a significant increase in posttest scores. Children demonstrated greater enthusiasm, focus, and engagement throughout the learning process. Canva’s visual and interactive elements helped simplify complex concepts, making them easier and more enjoyable to learn.The findings suggest that Canva is an effective medium for enhancing nationalism awareness among Indonesian children abroad. This study highlights the importance of using engaging digital tools in character and civic education, particularly in multicultural and global contexts.